1991
DOI: 10.3382/ps.0702040
|View full text |Cite
|
Sign up to set email alerts
|

Organ Growth and Digestive Enzyme Levels to Fifteen Days of Age in Lines of Chickens Differing in Body Weight

Abstract: Weights of internal organs and levels of digestive enzymes were obtained through the first 15 days posthatch for cockerels from three lines of chickens known to differ greatly in body weight. On Day 15 body weights from the fastest growing line were eight times greater than those from the slowest growing line. Differences among lines were found for weights at hatching and for growth patterns (both absolute and relative to body weight) of the vitelline residue, heart, lungs, liver, pancreas, crop, proventriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 8 publications
8
63
0
15
Order By: Relevance
“…Differences in enzyme production between high and low body weight lines have been reported in chickens at the same chronological age (Nir et al 1987;O'Sullivan et al 1992a). Elsewhere, it has been found that birds selected for high body weight showed higher intestinal and pancreatic trypsin and amylase levels expressed relative to the intestinal contents (Nitsan et al 1991;Dunnington and Siegel 1995). Tolkamp et al (2010) recently provided further evidence in support of the view that enzymatic production can also be altered via selection for growth rate and feed efficiency (Pym 1985;Doeschate et al 1993) but not by selection for leanness (Leclercq and Saadoun 1982).…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 69%
See 2 more Smart Citations
“…Differences in enzyme production between high and low body weight lines have been reported in chickens at the same chronological age (Nir et al 1987;O'Sullivan et al 1992a). Elsewhere, it has been found that birds selected for high body weight showed higher intestinal and pancreatic trypsin and amylase levels expressed relative to the intestinal contents (Nitsan et al 1991;Dunnington and Siegel 1995). Tolkamp et al (2010) recently provided further evidence in support of the view that enzymatic production can also be altered via selection for growth rate and feed efficiency (Pym 1985;Doeschate et al 1993) but not by selection for leanness (Leclercq and Saadoun 1982).…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 69%
“…Selection for higher growth rate has led to a lower degree of maturity at slaughter and this affects the size of different organs at any given age with some organs, such as those that make up the digestive tract, being genetically predisposed to maturing sooner than others (Katanbaf et al 1988;Mitchell and Smith 1991;Nitsan et al 1991;Nir et al 1993). Despite the digestive system maturing more quickly in modern breeds compared to old-type ones, the digestive system has reduced in size relative to body weight at a comparable age.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitsan et al (1991) observed no differences in absolute or relative pancreas weights between the lines on DOH (S 30 generation). Similarly, relative pancreas weights between LWS and HWS did not differ on d 8 or 21 (O'Sullivan et al, 1992).…”
Section: Pancreas Weight and Histologymentioning
confidence: 89%
“…In regard to pancreas physiology, the greater islet size but reduced total islet mass (% BW) in HWS than LWS chickens at selection age may be indicative of a state similar to that observed in obesity. The similarities in pancreas weights between young LWS and HWS chickens previously reported (Nitsan et al, 1991;O'Sullivan et al, 1992), could suggest that the decreased islet mass observed in selection age HWS chickens develops later in life as a result of chronic obesity. It is also possible that the observed results are associated with the 25 generations of continued genetic selection since the S 30 generation.…”
Section: Pancreas Weight and Histologymentioning
confidence: 91%